2022
DOI: 10.5713/ab.21.0183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed restriction on the maintenance energy requirement of broiler breeders

Abstract: Objective: This study aimed to evaluate the effect of the ad libitum and restricted feeding regimen on fasting heat production (FHP) and body composition.Methods: Twelve Hubbard broilers breeders were selected with the same body weight and submitted in two feeding regimes: Restricted (T1) with feed intake of 150 g/bird/d and ad libitum (T2). The birds were randomly distributed on the treatments in two runs with three replications per treatment (per run). The birds were adapted to the feed regimens for ten days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…Furthermore, the data on feed intake confirmed that broilers provided with ad libitum feeding consumed consistently higher amounts of feed compared to those under restricted feeding. This finding is in line with expectations, as the ad libitum group had unlimited access to feed, whereas the restricted group had their feed intake limited by predetermined amounts 15 . Higher feed intake in the ad libitum group is expected to contribute to their superior growth rates.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the data on feed intake confirmed that broilers provided with ad libitum feeding consumed consistently higher amounts of feed compared to those under restricted feeding. This finding is in line with expectations, as the ad libitum group had unlimited access to feed, whereas the restricted group had their feed intake limited by predetermined amounts 15 . Higher feed intake in the ad libitum group is expected to contribute to their superior growth rates.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, reports have demonstrated the variation of FHP due to methodological or procedural approaches. For example, Teofilo et al (2022) found similar values (296 kJ/kg 0.75 *d) to those obtained here in a restricted-fed broiler breeder using the indirect calorimetry method.…”
Section: Discussionsupporting
confidence: 87%
“…The variations found are attributed to environmental factors such as floor production or cages that interfere with the energy cost of physical activity for floor-reared birds ( Sakomura et al, 2003 ). As mentioned by van der Klein et al, 2020 , Rabello et al (2004) , and Teofilo et al (2022) , the maintenance requirement is affected by factors like environmental temperature and feeding program (restricted or ad libitum) and have statistical implication when the feeding level is altered. Therefore, this method was questioned in other species ( Koong et al, 1985 ; de Lange et al, 2006 ; Labussière et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while similar BW can be achieved with different dietary ME levels, body composition might differ, especially when the ratio of other nutrients (crude protein and AA) is kept constant across the different dietary energy levels. Similarly to dietary energy, feed restriction tends to show higher feed efficiency due to decreased maintenance requirements and fat deposition [11,52]. Although no maintenance requirements and fat deposition results are presented in the present report, the greater feed efficiency in the restricted-fed compared to ad libitum-fed birds corroborates the results of the present study.…”
Section: Feed Conversion Ratiosupporting
confidence: 86%
“…However, feed restriction programs might be helpful for optimal profit yield instead of optimal reproductive performance [10]. Restricted pullets have lower maintenance requirements, consuming less feed and being more efficient [11]. On the other hand, severe feed restriction during the rearing period can limit nutrient intake and decrease BW and egg production [12,13].…”
Section: Introductionmentioning
confidence: 99%